Comportamento elastodinamico di meccanismi in catena chiusa bilanciati: analisi numerica e sperimentale di un quadrilatero articolato - Martini, Alberto <1981> (Alma Mater Studiorum - Università di Bologna, 2011)
The study presented in this work deals with the investigation of the effects produced by two common techniques of static balancing on the dynamic performances of closed-chain linkages, taking into account the compliance of the mechanism components. The long-term goal of the research consists in determining an optimal balancing strategy for parallel spatial manipulators. The present contribution is a starting point and it focuses on the planar four-bar linkage, intended as the simplest example of closed-chain mechanism. The elastodynamic behaviour of an unbalanced four-bar linkage and two balanced ones, respectively obtained by mass and elastic balancing, is investigated by means of both numerical simulations and experimental tests. The purpose of this work is to obtain preliminary results, to be refined and broadened in future developments